1993
DOI: 10.2224/sbp.1993.21.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Socially Restrictive and Authoritarian Attitudes Toward Mental Patients in University Students

Abstract: Ninety-two university students (55 women; 37 men) participated in a study of the relationship between authoritarian and socially restrictive attitudes toward mental patients and the variables of trait -anxiety, self-esteem, locus of control, age, and gender. Results of multivariate analyses showed that individuals who score high in authoritarianism tend to be young, male, and believers in chance and fate (external locus of control). A similar pattern was found for social restrictiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Moreover, given the need to remove men from the analysis population due to their small numbers, the sample is not truly representative of an overall nursing student population. Because female students may be less likely to view mental illness negatively than their male peers, 24 if males had been included in our analysis, more agreement with stigmatizing statements about AN could have emerged. Finally, as with all self-report questionnaires, participants may have responded in a way that they believed to be socially desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, given the need to remove men from the analysis population due to their small numbers, the sample is not truly representative of an overall nursing student population. Because female students may be less likely to view mental illness negatively than their male peers, 24 if males had been included in our analysis, more agreement with stigmatizing statements about AN could have emerged. Finally, as with all self-report questionnaires, participants may have responded in a way that they believed to be socially desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Attitudes function as a protective mechanism; namely individuals try to develop attitudes which will ease themselves and protect their own egos (7). In the present study, while counselling teachers considered mental illnesses and patients with them as subjects of shame and, dangerous, and poorly successful in interpersonal relationships, their education, occupation of being a mental health counselor, their social class might cause masking of their personal unfavorable beliefs, as it was the expected favorable attitude them from (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 82%
“…In general, it was observed that people from high social classes, young, and well-educated were more tolerant about individuals with mental illnesses (27,28). In another study, although attitudes of these people to mental illnesses were more favorable, it was proposed that this might be because people desired to be admired more (25).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations